3D-Printed Guide for Thumb Carpometacarpal Prosthesis in Low Bone Stock - Matiotti-Neto, Mario; Ruggiero, Gustavo Mantovani (Journal of Wrist Surgery, 2025)
Thumb carpometacarpal (CMC) joint arthritis is a common and limiting condition of the hand in the elderly population. This can often lead to Z-deformity and compromised grip strength. While prosthetic arthroplasty has improved treatment outcomes, patients with low bone stock still present technical challenges. Standard techniques may risk poor implant positioning, fracture, and loosening. This case report describes the use of a novel technique with the use of a patent-specific three-dimensional (3D)-printed guide to enhance surgical precision.A 77-year-old female with Eaton stage IV CMC arthritis presented with advanced trapezium collapse, adduction, and Z-deformity of her left thumb. Preoperative computed tomography scan revealed a severely compromised trapezium with a medium height of 7 mm. A custom 3D-printed polylactic acid guide was designed to optimize cup positioning for MAÏA prothesis implantation. Accurate guidewire placement was obtained through the use of the 3D-printed guide, reducing the risk of malposition. Postoperative imaging confirmed correct implant alignment without lucency at 12 weeks' postoperative.In previous studies, the use of 3D-printed guides show reduced intraoperative time and errors. However, challenge remains on the widespread adoption of the method, due to increased cost and high production time outside the operating room.This case illustrates that 3D-printed patient-specific guides may enhance implant placement accuracy in CMC arthroplasty, particularly in patients with compromised bony anatomy. The guide facilitated safer reaming of the trapezium and optimized long-term implant stability. Despite concerns about cost, production time, and required technical expertise, such technology holds promise for select, high-risk cases.
Keywords: thumb; arthritis; arthroplasty; 3D-printing